Effects of emergency rescue clothing on wearers' physiological and perceptual responses in hot-humid environments - Qian, Yazhuo; Yuan, Mengqi; Yan, Ke; Li, Yayun; Wang, Xuefan; Wu, Hao (Frontiers in Public Health, 2025)
IntroductionTo improve the work efficiency and reduce heat-related illness of emergency rescue personnel, the effects of emergency rescue clothing on physiological and perceptual responses were investigated.MethodsThirteen participants were recruited to perform human trials in a climate chamber wherein the ambient temperature and relative humidity was controlled at 35°C and 75%, and 25°C and 65%, respectively. Moreover, participants wearing emergency rescue clothing (ERC group) and T-shirts and shorts (CON group) walked at 4 and 6 km/h on a treadmill. During the trials, physiological responses and subjective responses were obtained, and then physiological strain index (PSI) and perceptual strain index (PeSI) were calculated.ResultsThe results showed significant differences between the ERC and the CON in parameters such as core temperature, mean skin temperature, heart rate, PSI, although some data differences were slightly. There was a positive correlation between PeSI and PSI, as well as between mean skin temperature and thermal sensation vote, with R values of 0.93 and 0.94 (ERC), respectively.DiscussionCorrelation analysis shows that PeSI had a potential to predict PSI. This study can replace complex and cumbersome physiological indicators by calculating the perception indicators of emergency response personnel working on site, promoting the development of the safety industry engaged in certain intensity physical labor in humid and hot environments.